GEOSTATISTICAL STUDY OF SURFACE SOIL PROPERTIES UNDER AN OIL PALM PLANTATION: 1 SEMI-VARIOGRAM - OYEDELE, D. J.; NURUDEEN , O. O.; AINA, P. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The spatial variability of selected surface soil properties was studied under an oil palm plantation by using geostatiscal concepts. Measurement were made on samples collected at 10 metres interval on a 10m x 10m grid from a plot of one hectare. Semi-variograms of the soil properties were computed and fitted to appropriate models by the least square method. This showed the variabilities in the soil properties to be anisotropically spatially  structured. Cross-variograms were also presented for gravel contents bulk density and cone index. The usefulness of this technique as aid in identifying the cause and the nature of variabilities soil properties are discussed.